"We are more scared of the power elites than the floods": Adaptive capacity and resilience of wetland community to flash flood disasters in Bangladesh. (October 2016) - Choudhury, Mahed-Ul-Islam; Haque, C. Emdad
Abstract: Studies on disaster risk reduction primarily centers on the research streams of vulnerability and resilience. The concept of adaptive capacity is central to both streams of study and has profound implications for disaster risk reduction. Drawing insights from both streams, we examined the adaptive capacity of wetland communities with regards to flash flood disasters. Focusing on societal dimensions, we investigated how the interplay of institutions, community power structures, and human agency shape adaptive capacity of wetland communities. We employed the "dominant-less dominant" research methodological framework, and followed a 4-tier study design: i) a household survey, ii) a semi-structured questionnaire survey, iii) oral history interviews, and iv) key informant interviews. Our findings revealed that wetland communities in the region are highly vulnerable to flash flood hazards. Local community members were conditioned, chiefly by the asymmetrical social power structure, to feel helpless in the face of natural disasters. Their reactive recovery measures have resulted in maladaptation and in their becoming passive towards risk mitigation for future floods. However, transformative patterns were also observed in a large proportion of the population, wherein community members modified or changed their behavior to achieve longer-term sustainability and risk mitigation. We concluded that in designing development interventions to enhance adaptive capacity, consideration must be given to the diverse range of skills and educational development among the local population.